An unusual and delayed complication of hyaluronic acid filler injection: a case report - Horriat, Narges (Case Reports Plast Surg Hand Surg, 2020)
48-year-old female with facial granulomatous nodules and fungal/bacterial infection after hyaluronic acid injection. She underwent anti-fungal/antibacterial therapy and local excision. The proposed mechanisms include inflammatory foreign body reaction and pathogen contamination. Providers must exercise caution with the use of facial fillers and demonstrate expertise in avoiding and managing potential complications.